Synthesis of the structure of technical condition of power electric circuit of electric locomotive automatic control system - Mokin, B. I.; Lobatiuk, Yu. A.; Zhukov, S. O. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The structure of the system of automatic monitoring of power circuits condition of electric locomotive VL80R is synthe-sized that allows to display on the scoreboard the probable cause of the problem and suggests a method of its elimination.